Myeloid interferon-γ receptor deficiency does not affect atherosclerosis in LDLR-/- mice. (March 2016) - Boshuizen, Marieke C.S.; Neele, Annette E.; Gijbels, Marion J.J.; van der Velden, Saskia; Hoeksema, Marten A.; Forman, Ruth A.; Muller, Werner; Van den Bossche, Jan; de Winther, Menno P.J.
Abstract: Background and aims: Atherosclerosis is a chronic lipid-driven inflammatory disease of the arterial wall. Interferon gamma (IFNγ) is an important immunomodulatory cytokine and a known pro-atherosclerotic mediator. However, cell-specific targeting of IFNγ or its signaling in atherosclerosis development has not been studied yet. As macrophages are important IFNγ targets, we here addressed the involvement of myeloid IFNγ signaling in murine atherosclerosis. Methods: Bone marrow was isolated from interferon gamma receptor 2 chain (IFNγR2) wildtype and myeloid IFNγR2 deficient mice and injected into lethally irradiated LDLR -/- mice. After recovery mice were put on a high fat diet for 10 weeks after which atherosclerotic lesion analysis was performed. In addition, the accompanying liver inflammation was assessed. Results: Even though absence of myeloid IFNγ signaling attenuated the myeloid IFNγ response, no significant differences in atherosclerotic lesion size or phenotype were found. Also, when examining the liver inflammatory state no effects of IFNγR2 deficiency could be observed. Conclusion: Overall, our data argue against a role for myeloid IFNγR2 in atherosclerosis development. Since myeloid IFNγ signaling seems to be nonessential throughout atherogenesis, it is important to understand the mechanisms by which IFNγ acts in atherogenesis. In the future new studies should be performed considering other cell-specific targets. Graphical abstract: Highlights: Attenuated IFNγ response in macrophages with interferon gamma signaling deficiency. Absence of myeloid interferon gamma signaling does not affect atherosclerosis. Myeloid interferon gamma receptor deficiency is dispensable in liver inflammation.